Integration of Higher Education Curriculum with Islamic Boarding Schools in the Perspective of Multicultural Islamic Education - Akhmad Sirojuddin; Maskuri Maskuri; Junaidi Ghoni (Nazhruna: Jurnal Pendidikan Islam, 2025)
Curriculum integration between Islamic Boarding Schools and Islamic Universities is an important issue in the context of Islamic education in Indonesia, the diversity of Indonesian culture requires a more inclusive and adaptive educational approach as an anticipation of the risk of losing students' social competence and as a solution to improving the character of religious and cultural values ​​as an effort to enhance the success of educational quality. This study aims to explore the dynamics of collaboration between Islamic boarding schools and universities in carrying out the process and the positive implications of integrating an educational curriculum that teaches religious knowledge, worldly skills, and multicultural values. Using a qualitative approach, data were obtained through observation, in-depth interviews, and document analysis related to both institutions' curricula and learning activities. The study results show that the formal and non-formal collaboration process between universities and Islamic boarding schools has succeeded in producing a curriculum that combines Islamic values, general skills, and cross-cultural knowledge, facilitating the exchange of experiences that enrich students' perspectives. The impact of this integration includes increasing attitudes of tolerance, respect for diversity, and deeper understanding; the quality of social interactions between both becomes more harmonious and open to differences. These findings highlight the importance of teaching multiculturalism in Islamic education, which is theoretical and applied in everyday life. The novelty of this study lies in the ability of Islamic educational institutions to integrate multicultural values ​​relevant to the pluralistic Indonesian context and contribute to the development of more adaptive and moderate student characters. This study recommends developing cross-institutional programs to strengthen curriculum integration and increase social impact.